Pemberdayaan Media Youtube â€œNussa Officialâ€ Sebagai Sarana Pengembangan Nilai Moral Dan Agama Pada Anak - Thorik Aziz (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
This study discusses the "Nussa Official" Youtube Media Empowerment as a Means of Developing Moral and Religious Values in Children. The method used in this study is qualitative content analysis with the type of field research (field research) which serves to describe the content, message characteristics, and draw conclusions from several Yotube Nussa Official video content that has messages of moral and religious values in children. The results of this study indicate that there are implications of empowering the Nussa Official YouTube media in developing moral and religious values in children. Among them are being able to make children accustomed to shaking hands with other people, teach honesty and function, get children used to praying before doing activities, teach children not to be arrogant, teach children to be sensitive to social relationships, teach children to relate to people who are not their relatives, teach children to respect each other, and get children to behave well in any circumstances.